GCC E procurement system - Chiweshe, Ronald (Midlands State University, 2020)
This research is aimed at development of an E Procurement System that is meant to assist the procurement department in procurement decision making processes. The researcher had proposed the idea of introducing a new system after discovering problems that were being experienced as a result of manual processes, some of the problems include; delays in procurement decision making, there was no a website to update suppliers about new tenders at Gweru City Council, there is no system in place for suppliers to check their tender status. In order to identify these problems the researcher had used various data finding methodologies which includes questionnaires, interviews and observations. After discovery of the weaknesses of the system which was in place the researcher then came up with a solution in form of an e-procurement decision support system. The system allows the procurement section to quickly come up with a procurement decision without holding any meeting as the system give the decision makers the capabilities to login into the system and access the decision that would be been automatically generated by the system basing on the data that would have been captured for the service providers. Objectives that had been stated were used as the guideline to the development of the project. These objectives were altered a bit due to the changing requirements of the system users and also the equipment available.